Open-Source Property A Free Casebook - Clowney, Stephen; Grimmelmann, James; Grynberg, Michael (Open textbook library., 2015)
Open Source Property: A Free Casebook is a free resource for instructors and students of the first-year Property Law course at American law schools, and anyone else with an interest in the subject.